2024
DOI: 10.1128/mmbr.00131-23
|View full text |Cite
|
Sign up to set email alerts
|

Hemophore-like proteins of the HmuY family in the oral and gut microbiome: unraveling the mystery of their evolution

Teresa Olczak,
Michał Śmiga,
Svetlana V. Antonyuk
et al.

Abstract: SUMMARY Heme (iron protoporphyrin IX, FePPIX) is the main source of iron and PPIX for host-associated pathogenic bacteria, including members of the Bacteroidota (formerly Bacteroidetes) phylum. Porphyromonas gingivalis , a keystone oral pathogen, uses a unique heme uptake (Hmu) system, comprising a hemophore-like protein, designated as the first member of the novel HmuY family. Compared to classical, secreted hemophores utilized by Gram-negative bacteria or near-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 241 publications
1
7
0
Order By: Relevance
“…Data obtained in our study showed that one of the P. gingivalis adaptive features can be assigned not only to better tolerance to oxygen and higher proteolytic activity but also to different properties of heme binding by HmuY Pg as compared to HmuY Pe . The strength of heme binding by HmuY proteins depends on the redox state of the external environment (Olczak et al, 2024) and based on our results is as follows: HmuY Pg >HmuY Pe >HmuY Tf . HmuY Pg , coordinating heme iron with two histidines, binds heme efficiently under both oxidizing and reducing conditions.…”
supporting
confidence: 54%
See 4 more Smart Citations
“…Data obtained in our study showed that one of the P. gingivalis adaptive features can be assigned not only to better tolerance to oxygen and higher proteolytic activity but also to different properties of heme binding by HmuY Pg as compared to HmuY Pe . The strength of heme binding by HmuY proteins depends on the redox state of the external environment (Olczak et al, 2024) and based on our results is as follows: HmuY Pg >HmuY Pe >HmuY Tf . HmuY Pg , coordinating heme iron with two histidines, binds heme efficiently under both oxidizing and reducing conditions.…”
supporting
confidence: 54%
“…Analysis of the overall three-dimensional experimentally solved (P. gingivalis HmuY Pg and T. forsythia HmuY Tf ) or theoretically predicted (other selected Porphyromonas species) protein structures revealed that HmuY proteins identified in the Porphyromonas species are highly similar to the P. gingivalis HmuY Pg (Figure 1D), with the highest similarities observed in the core region (S ́miga et al, 2023a). As in so far characterized HmuY proteins (Olczak et al, 2024), the main differences in HmuY proteins identified in Porphyromonas species are visible in the structure of heme-binding pockets and differ mainly in the size of the entrance of the heme-binding pocket (Figure 1D). The data shown in Figure 1 allowed us to verify the spatial location of predicted amino acids involved in heme binding in HmuY homologs in analyzed Porphyromonas species.…”
Section: P Endodontalis Hmuy Pe Binds Hemementioning
confidence: 55%
See 3 more Smart Citations